Dual vs. mono antiplatelet therapy for acute ischemic stroke or transient ischemic attack with evidence of large artery atherosclerosis - Lin, Chun-Jen; Tseng, Tzu-Yun; Saver, Jeffrey L. (Frontiers in Neurology, 2022)
Background and Purpose: Current evidences support the short-term use of dual antiplatelet (DAPT) in minor ischemic stroke or transient ischemic attack (TIA) based on the studies performed in patients with a broad range of non-cardioembolic stroke mechanisms. However, the efficacy and safety of DAPT use in ischemic stroke patients with large artery atherosclerosis (LAA) are still uncertain. We undertook a systemic search and formal meta-analysis to compare DAPT vs mono-antiplatelet therapy (MAPT) in patients with etiology specifically presumed to be symptomatic LAA. Methods: We conducted a systemic online search for completed randomized controlled trials that 1) compared DAPT vs MAPT in patients with acute ischemic stroke or TIA, 2) were confined to or had available subgroup data regarding population with symptomatic extra- or intracranial cervico-cerebral artery stenosis. Study-level meta-analysis was performed for outcomes including ischemic stroke (IS) recurrence, intracranial hemorrhage (ICH), and major bleeding with Mantel-Haenszel method and random effect models, and was described as risk difference (RD) and 95% confidence interval (CI). Results: Ten trials including 5,004 patients were pooled. Comparing to MAPT, DAPT significantly reduced IS recurrence (5.99% vs 9.55%, RD: -3%, 95% CI: -5% to 0%). Across all agents, out of 100 treated patients, 3 fewer had recurrent ischemic stroke with DAPT. The safety endpoints including ICH (0.28% vs 0.32%, RD: 0%, 95% CI: -0% to 0%) and major bleeding (0.73% vs 0.51%, RD: 0%, 95% CI: -0% to 0%) did not differ significantly. Conclusions: In patients with symptomatic large artery extracranial or intracranial atherosclerosis, DAPT was superior to MAPT in preventing IS recurrence without increasing bleeding risks. The optimal DAPT regimens and duration of treatment in this population need to be clarified in further studies.